Endophytic animations to blossom sub-Saharan agriculture - Kaushal, M. (Elsevier, 2020)
Sub-Saharan regions are exceptional ecosystems in which crop plants suffer from dual impairment of low soil fertility and gate crasher phytopathogens. Worldwide common practice of intensive agriculture with the use of agrochemical inputs is ground lacking truth for the small holder farmers of Sub-Saharan Africa (SSA) that are entirely committed on agriculture for their livelihoods. Considering economically and feasibility terms of food security for small holder farmers, an urgent switching on alternative is a compulsion. From decades, endophytic microbiome has been linked to host for improved production and maintenance of plant health. These novel microbial troops inhabit plant tissues, thus receive shelter and more access to nutrients. With these supplementary benefits endophytes are more superior as compared to another microbiota. In present review we focused the hardball played by endophytes and their mechanisms in plant growth and development. We also depict the endophytic significance in overcoming the issues of food security in the crops that economically sound and ensure long-term sustainability for the small holder farmers of SSA.